2020
DOI: 10.1371/journal.pone.0238496
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease and relapsing fever in Mexico: An overview of human and wildlife infections

Abstract: Lyme borreliosis and Relapsing fever are considered emerging and re-emerging diseases that cause major public health problems in endemic countries. Epidemiology and geographical distribution of these diseases are documented in the US and in Europe, yet in Mexico, studies are scarce and scattered. The aims of this study were (1) to present the first confirmatory evidence of an endemic case of Lyme disease in Mexico and (2) to analyze the epidemiological trend of these both diseases by compiling all the informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 78 publications
0
20
0
1
Order By: Relevance
“…This disease has previously been reported in JBR in other species, such as wild carnivores and domestic animals [7]. Colunga-Salas et al [38], reviewed cases reported in Mexico from 1930 to 2020; 29.5% were reports on humans, while 70.5% reported an animal species. They identified six Borrelia species: three responsible for Relapsing Fever (B. duguessi, B. mazzottii and B. turicatae) and three more are responsible for Lyme borreliosis (B. afzelii, B. burgdorferi s. s. and B. garini).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This disease has previously been reported in JBR in other species, such as wild carnivores and domestic animals [7]. Colunga-Salas et al [38], reviewed cases reported in Mexico from 1930 to 2020; 29.5% were reports on humans, while 70.5% reported an animal species. They identified six Borrelia species: three responsible for Relapsing Fever (B. duguessi, B. mazzottii and B. turicatae) and three more are responsible for Lyme borreliosis (B. afzelii, B. burgdorferi s. s. and B. garini).…”
Section: Discussionmentioning
confidence: 81%
“…Wild vertebrates are associated with several enzootic cycles of tick-borne pathogens contributing to the increase of ticks and TBDs in North America, playing an important role in the maintenance and transmission of zoonoses to livestock, humans, and other wildlife [34]. A more than two-fold increase in TBDs has been observed from 2004 (>22,000 cases) to 2016 (>48,000 cases) in the USA alone [35], and up to 476,000 people per year are infected with Lyme disease [36], with reports in both Mexico and USA [37][38][39][40] involving wild animals [41][42][43][44][45]. Furthermore, ticks and TBDs have evolved, adapting themselves to new vectors and vectors have adapted to new hosts; for instance, Amblyoma immitator has recently been proposed as a RMSF vector [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BYS is widespread in Brazil and in the Amazon rainforest, but also in Colombia, Peru, Venezuela, Ecuador, Bolivia, Guyana, Suriname and French Guiana [255]. In Mexico, Borrelia burgdorferi s.s. has also been described in Ambliomma cajennense, in ticks taken from the bull (Bos taurus) [256]. Cases of borreliosis have also been described in Cuba, diagnosed for the clinical picture and the positivity of anti-Borrelia antibodies and transmitted by Amblyomma cajennense, similar to BYS [257].…”
Section: Borrelia Lyme Group-baggio-yoshinari Group (Bys): the Brazilian Lyme-disease-like Illnessmentioning
confidence: 97%
“…Since RF is considered a forgotten and neglected tropical disease, and given the small number of cases reported by the Mexican Ministry of Health, it is conceivable that many patients who have a fever of unknown origin are suffering from RF [ 70 ]. In Mexico, the following specificities of Borrelia tick association are observed: Ornithodoros turicata with B. turicatae , Ornithodoros duguesi with B. duguesii , and Ornithodoros talaje with B. mazzottii [ 71 ]. In Brazil, Venezuela, Colombia, and Panama STBRF is caused by Borrelia venezualensis , which is transmitted by Ornithodoros rudis [ 66 ].…”
Section: Endemic Relapsing Fever Borreliosis (Stbrf)mentioning
confidence: 99%